2009
DOI: 10.1080/13697130802626958
|View full text |Cite
|
Sign up to set email alerts
|

Food groups and risk of forearm fractures in postmenopausal women in Chengdu, China

Abstract: This is the first report indicating that the levels of vegetable and cereal intake, and that meeting WHO recommendations for vegetable and fruit intake, are associated with a decrease in the risk of forearm fractures in Chinese postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…The potential negative effect of a diet of low quality might be offset by a greater waist circumference (57), because some studies suggest that those with a higher BMI or waist circumference have lower BTMs (58)(59). Finally, although few observational studies have reported protective effects of healthy dietary patterns on bone health in postmenopausal women (11,(60)(61)(62)(63), these findings were based on BMD or fracture data, which may indicate long-term effect of diet on bone health. Dietary interventions in postmenopausal women have failed to support the beneficial effect of healthy eating on bone status in the postmenopausal years (12,13,64,65).…”
Section: No Relations Between Hei-2005 and Btmsmentioning
confidence: 99%
“…The potential negative effect of a diet of low quality might be offset by a greater waist circumference (57), because some studies suggest that those with a higher BMI or waist circumference have lower BTMs (58)(59). Finally, although few observational studies have reported protective effects of healthy dietary patterns on bone health in postmenopausal women (11,(60)(61)(62)(63), these findings were based on BMD or fracture data, which may indicate long-term effect of diet on bone health. Dietary interventions in postmenopausal women have failed to support the beneficial effect of healthy eating on bone status in the postmenopausal years (12,13,64,65).…”
Section: No Relations Between Hei-2005 and Btmsmentioning
confidence: 99%
“…Eight studies were included for this systematic review. Two studies were RCTs [34,35], three were cross-sectional studies [36][37][38], one was a prospective cohort study [39], one a case-control study [40], and one cohort study reported cross-sectional as well as longitudinal data [41]. The reasons for exclusion of studies are also outlined in Fig.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The intake levels and assessment of F&V intake as well as follow-up time varied among studies. Four studies reported outcomes for F&V combined [34][35][36]41]; all others reported fruits separate from vegetables as well as combined [37][38][39][40]. Only one study reported examining the effect of subcategories of fruits or vegetables (citrus fruits, green leafy vegetables, etc.)…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, lifestyle modifications have been undertaken, such as changes in exercise and diet. A number of epidemiological studies have identified that higher fruit and vegetable intake was associated with higher BMD (21-25) and a lower fracture risk (26) in postmenopausal women. While the mechanisms underlying these bone-protective effects are yet to be fully elucidated, antioxidative nutrients and phytochemicals, including vitamin C, carotenoids and polyphenols, which are contained in fruits and vegetables, may improve bone health by scavenging ROS (27).…”
Section: Introductionmentioning
confidence: 99%